Glucose Metabolism in Children With Growth Hormone Deficiency - Ciresi, Alessandro; Giordano, Carla (Frontiers in Endocrinology, 2018)
Background The growth hormone (GH)/insulin-like growth factor 1 (IGF-1) axis has a fundamental impact on glucose metabolism. Therefore, both untreated GH deficiency (GHD) and GH treatment (GHT) may be associated with some metabolic alterations, although the abnormalities of glucose metabolism have been investigated by relatively few studies as main outcomes. Aim The present review summarizes the available data on glucose metabolism in children with GHD, providing an overview of the current state of the art in order to better clarify the real metabolic impact of GHD and GHT. Methods Among all the existing studies, we evaluated all original studies that fulfilled our criteria for analysis reporting parameters of glucose metabolism as the primary or secondary objective. Results The reported impact of GHD per se on glucose metabolism is quite homogeneous, with the majority of studies reporting no significant difference in metabolic parameters between GHD children and controls. Conversely, GHT proves to be more frequently associated with a subtle form of insulin resistance, while both fasting glucose and HbA1c levels remain almost always within the normal range. Conclusion The different methods to study glucose metabolism, the heterogeneity of the populations evaluated, the different doses of GH used together with the variable duration of follow-up may be responsible for discrepancy in the results. Long-term longitudinal studies having glucose homeostasis as their primary outcome are still needed in order better to clarify the real metabolic impact of GHD and GHT in children.